2018
DOI: 10.1002/ecy.2512
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the paradox of clumped seed dispersal: positive density and distance dependence in a bat‐dispersed species

Abstract: One of the hypothesized benefits of seed dispersal is to escape density- and distance-responsive, host-specific, natural enemies near maternal plants where conspecific seed and seedling densities are high. Such high conspecific neighbor densities typically result in lower offspring growth and survival (i.e., negative density-dependent effects), yet many dispersal modes result in clumped seed distributions. New World leaf-nosed bats transport fruits to their feeding roosts and deposit seeds, thereby creating hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Interestingly no seedlings of S. purpurea were recorded directly underneath conspecific trees possibly due to strong negative density dependent effects (e.g. seed predation, interspecific competition) [70][71][72] reinforcing the idea that J-C effects strongly shape S. purpurea seedling recruitment.…”
Section: Size Class B Log F (1) Spmentioning
confidence: 79%
“…Interestingly no seedlings of S. purpurea were recorded directly underneath conspecific trees possibly due to strong negative density dependent effects (e.g. seed predation, interspecific competition) [70][71][72] reinforcing the idea that J-C effects strongly shape S. purpurea seedling recruitment.…”
Section: Size Class B Log F (1) Spmentioning
confidence: 79%
“…While strengthening aggregation might be expected to drive more intense negative density dependence, Bagchi et al () found that despite local aggregation increasing under defaunation, there was no commensurate increase in self‐thinning. Likewise, Sugiyama et al () found that although bat dispersal leads to high local seedling densities the benefits of deposition in favorable sites outweighs negative density dependence. Nevertheless, negative density dependent effects are important in some contexts and may change the detectability and nature of any change in plant spatial distribution.…”
Section: Methodsmentioning
confidence: 99%
“…However, seeds dispersed in feces of large frugivores may also suffer negative density‐dependence as many germinants may arise from a single clump. In such cases, chemical or mechanical defenses may facilitate resistance to density‐dependent effects (Howe, ) or other benefits may out‐weigh local density effects (Sugiyama, Comita, Masaki, Condit, & Hubbell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seed dispersal is important in allowing seeds to reach new establishment sites (especially under climate change scenarios) [6][7][8] , and because of negative density and distance dependent mortality of seeds and seedlings [9][10][11][12] . Also, long distance dispersal may affect the rates of population migration and contributes to maintaining connectivity among plant populations in fragmented landscapes and across large spatial scales 13,14 .…”
Section: Oilbirds Disperse Large Seeds At Longer Distance Than Extincmentioning
confidence: 99%